City & Spectacle: A Vision of Lisbon Before the 1755 Great Earthquake - Rodrigues, Paulo Simões (2017)
City & Spectacle: a vision of pre-earthquake Lisbon consists of a virtual recrea on of the city of Lis- bon on the eve of the great earthquake of 1 November 1755, giving shape to a laboratory model for research into the city’s history. As its star ng point the project has the virtual recrea on of one the most emblema c of spaces from 18th century Lisbon, the Royal Opera House, which disappeared during the 1755 earthquake. The recrea on of the Opera House was developed in the scope of the commemora- ons of the 250th anniversary of the 1755 catastrophe as an a empt to restore this space of the highest ar s c quality to memory and to return it to the inventory of the Portuguese heritage of architectural history.1 Using Second Life® technology it was possible to put forward a model of both the struc- ture and interiors of the Opera House as well as its anima on combined with a small piece of the opera presented at the inaugura on of the building in April 1755. The public presenta on of this virtual model at the conference 1755: Catástrofe, memória e arte (1755: catastrophe, memory and art), which took place at the Centro de Estudos Compara- stas, Universidade de Lisboa, led to a debate on the study and cri cal analysis of documentary sources and their selec on and applica on on recrea ons using virtual world technology. It also emphasized the need to extend the research on pre-earthquake Lisbon.